Jean Rhys`s Wide Sargasso Sea as a “Writing Back” Of Charlotte Brontë`s Jane Eyre - Tahmid, Aahnaf (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.